CO2‐Philic Separation Membrane: Deep Eutectic Solvent Filled Graphene Oxide Nanoslits. Issue 49 (23rd October 2019) - Lin, Hanqing; Gong, Ke; Ying, Wen; Chen, Danke; Zhang, Jun; Yan, Youguo; Peng, Xinsheng
Abstract : CO2 capture and sequestration is an energy‐intensive industry to deal with the global greenhouse effect. Membrane separation is considered a cost‐effective method to mitigate the emission of CO2 . Though good separation performance and stability have been reported, supported ionic liquid membranes are still not widely applied for CO2 separation due to the high cost. As a novel analogous solvent to ionic liquid, deep eutectic solvent retains the excellent merits of ionic liquid and is cheap with facile preparation. Herein, a highly CO2 ‐philic separation membrane is constructed by nanoconfining choline chloride/ethylene glycol (ChCl/EG) deep eutectic solvent into graphene oxide nanoslits. Molecular dynamic simulation results indicate that the confinement makes a difference to the structure of the nanoconfined ChCl/EG liquid from their bulk, which remarkably facilitates CO2 transport. By tuning the molar ratio of ChCl/EG and thickness of the membrane, the resultant membrane exhibits outstanding separation performance for CO2 with excellent selectivity over other light gases, good long‐term durability, and thermal stability. This makes it a promising membrane for selective CO2 separation. Abstract : A CO2 ‐philic membrane is constructed by filling choline chloride/ethylene glycol (ChCl/EG) deep eutectic solvent into graphene oxide nanoslits (GO‐SDESM), with prominent CO2 selectivity from other light gases (N2, CH4, and H2 ) and excellent stability.